123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191192193194195196197198199200201202203204205206207208209210211212213214215216217218219220221222223224225226227228229230231232233234235236237238239240241242243244245246247248249250251252253254255256257258259260261262263264265266267268269270271272273274275276277278279280281282283284285286287288289290291292293294295296297298299300301302303304305306307308309310311312313314315316317318319320321322323324325326327328329330331332333334335336337338339340341342343344345346347348349350351352353354355356357358359360361362363364365366367368369370371372373374375376377378379380381382383384385386387388389390391392393394395396397398399400401402403404405406407408 |
- """Test modules.py code."""
- from sympy.polys.agca.modules import FreeModule, ModuleOrder, FreeModulePolyRing
- from sympy.polys import CoercionFailed, QQ, lex, grlex, ilex, ZZ
- from sympy.abc import x, y, z
- from sympy.testing.pytest import raises
- from sympy.core.numbers import Rational
- def test_FreeModuleElement():
- M = QQ.old_poly_ring(x).free_module(3)
- e = M.convert([1, x, x**2])
- f = [QQ.old_poly_ring(x).convert(1), QQ.old_poly_ring(x).convert(x), QQ.old_poly_ring(x).convert(x**2)]
- assert list(e) == f
- assert f[0] == e[0]
- assert f[1] == e[1]
- assert f[2] == e[2]
- raises(IndexError, lambda: e[3])
- g = M.convert([x, 0, 0])
- assert e + g == M.convert([x + 1, x, x**2])
- assert f + g == M.convert([x + 1, x, x**2])
- assert -e == M.convert([-1, -x, -x**2])
- assert e - g == M.convert([1 - x, x, x**2])
- assert e != g
- assert M.convert([x, x, x]) / QQ.old_poly_ring(x).convert(x) == [1, 1, 1]
- R = QQ.old_poly_ring(x, order="ilex")
- assert R.free_module(1).convert([x]) / R.convert(x) == [1]
- def test_FreeModule():
- M1 = FreeModule(QQ.old_poly_ring(x), 2)
- assert M1 == FreeModule(QQ.old_poly_ring(x), 2)
- assert M1 != FreeModule(QQ.old_poly_ring(y), 2)
- assert M1 != FreeModule(QQ.old_poly_ring(x), 3)
- M2 = FreeModule(QQ.old_poly_ring(x, order="ilex"), 2)
- assert [x, 1] in M1
- assert [x] not in M1
- assert [2, y] not in M1
- assert [1/(x + 1), 2] not in M1
- e = M1.convert([x, x**2 + 1])
- X = QQ.old_poly_ring(x).convert(x)
- assert e == [X, X**2 + 1]
- assert e == [x, x**2 + 1]
- assert 2*e == [2*x, 2*x**2 + 2]
- assert e*2 == [2*x, 2*x**2 + 2]
- assert e/2 == [x/2, (x**2 + 1)/2]
- assert x*e == [x**2, x**3 + x]
- assert e*x == [x**2, x**3 + x]
- assert X*e == [x**2, x**3 + x]
- assert e*X == [x**2, x**3 + x]
- assert [x, 1] in M2
- assert [x] not in M2
- assert [2, y] not in M2
- assert [1/(x + 1), 2] in M2
- e = M2.convert([x, x**2 + 1])
- X = QQ.old_poly_ring(x, order="ilex").convert(x)
- assert e == [X, X**2 + 1]
- assert e == [x, x**2 + 1]
- assert 2*e == [2*x, 2*x**2 + 2]
- assert e*2 == [2*x, 2*x**2 + 2]
- assert e/2 == [x/2, (x**2 + 1)/2]
- assert x*e == [x**2, x**3 + x]
- assert e*x == [x**2, x**3 + x]
- assert e/(1 + x) == [x/(1 + x), (x**2 + 1)/(1 + x)]
- assert X*e == [x**2, x**3 + x]
- assert e*X == [x**2, x**3 + x]
- M3 = FreeModule(QQ.old_poly_ring(x, y), 2)
- assert M3.convert(e) == M3.convert([x, x**2 + 1])
- assert not M3.is_submodule(0)
- assert not M3.is_zero()
- raises(NotImplementedError, lambda: ZZ.old_poly_ring(x).free_module(2))
- raises(NotImplementedError, lambda: FreeModulePolyRing(ZZ, 2))
- raises(CoercionFailed, lambda: M1.convert(QQ.old_poly_ring(x).free_module(3)
- .convert([1, 2, 3])))
- raises(CoercionFailed, lambda: M3.convert(1))
- def test_ModuleOrder():
- o1 = ModuleOrder(lex, grlex, False)
- o2 = ModuleOrder(ilex, lex, False)
- assert o1 == ModuleOrder(lex, grlex, False)
- assert (o1 != ModuleOrder(lex, grlex, False)) is False
- assert o1 != o2
- assert o1((1, 2, 3)) == (1, (5, (2, 3)))
- assert o2((1, 2, 3)) == (-1, (2, 3))
- def test_SubModulePolyRing_global():
- R = QQ.old_poly_ring(x, y)
- F = R.free_module(3)
- Fd = F.submodule([1, 0, 0], [1, 2, 0], [1, 2, 3])
- M = F.submodule([x**2 + y**2, 1, 0], [x, y, 1])
- assert F == Fd
- assert Fd == F
- assert F != M
- assert M != F
- assert Fd != M
- assert M != Fd
- assert Fd == F.submodule(*F.basis())
- assert Fd.is_full_module()
- assert not M.is_full_module()
- assert not Fd.is_zero()
- assert not M.is_zero()
- assert Fd.submodule().is_zero()
- assert M.contains([x**2 + y**2 + x, 1 + y, 1])
- assert not M.contains([x**2 + y**2 + x, 1 + y, 2])
- assert M.contains([y**2, 1 - x*y, -x])
- assert not F.submodule([1 + x, 0, 0]) == F.submodule([1, 0, 0])
- assert F.submodule([1, 0, 0], [0, 1, 0]).union(F.submodule([0, 0, 1])) == F
- assert not M.is_submodule(0)
- m = F.convert([x**2 + y**2, 1, 0])
- n = M.convert(m)
- assert m.module is F
- assert n.module is M
- raises(ValueError, lambda: M.submodule([1, 0, 0]))
- raises(TypeError, lambda: M.union(1))
- raises(ValueError, lambda: M.union(R.free_module(1).submodule([x])))
- assert F.submodule([x, x, x]) != F.submodule([x, x, x], order="ilex")
- def test_SubModulePolyRing_local():
- R = QQ.old_poly_ring(x, y, order=ilex)
- F = R.free_module(3)
- Fd = F.submodule([1 + x, 0, 0], [1 + y, 2 + 2*y, 0], [1, 2, 3])
- M = F.submodule([x**2 + y**2, 1, 0], [x, y, 1])
- assert F == Fd
- assert Fd == F
- assert F != M
- assert M != F
- assert Fd != M
- assert M != Fd
- assert Fd == F.submodule(*F.basis())
- assert Fd.is_full_module()
- assert not M.is_full_module()
- assert not Fd.is_zero()
- assert not M.is_zero()
- assert Fd.submodule().is_zero()
- assert M.contains([x**2 + y**2 + x, 1 + y, 1])
- assert not M.contains([x**2 + y**2 + x, 1 + y, 2])
- assert M.contains([y**2, 1 - x*y, -x])
- assert F.submodule([1 + x, 0, 0]) == F.submodule([1, 0, 0])
- assert F.submodule(
- [1, 0, 0], [0, 1, 0]).union(F.submodule([0, 0, 1 + x*y])) == F
- raises(ValueError, lambda: M.submodule([1, 0, 0]))
- def test_SubModulePolyRing_nontriv_global():
- R = QQ.old_poly_ring(x, y, z)
- F = R.free_module(1)
- def contains(I, f):
- return F.submodule(*[[g] for g in I]).contains([f])
- assert contains([x, y], x)
- assert contains([x, y], x + y)
- assert not contains([x, y], 1)
- assert not contains([x, y], z)
- assert contains([x**2 + y, x**2 + x], x - y)
- assert not contains([x + y + z, x*y + x*z + y*z, x*y*z], x**2)
- assert contains([x + y + z, x*y + x*z + y*z, x*y*z], x**3)
- assert contains([x + y + z, x*y + x*z + y*z, x*y*z], x**4)
- assert not contains([x + y + z, x*y + x*z + y*z, x*y*z], x*y**2)
- assert contains([x + y + z, x*y + x*z + y*z, x*y*z], x**4 + y**3 + 2*z*y*x)
- assert contains([x + y + z, x*y + x*z + y*z, x*y*z], x*y*z)
- assert contains([x, 1 + x + y, 5 - 7*y], 1)
- assert contains(
- [x**3 + y**3, y**3 + z**3, z**3 + x**3, x**2*y + x**2*z + y**2*z],
- x**3)
- assert not contains(
- [x**3 + y**3, y**3 + z**3, z**3 + x**3, x**2*y + x**2*z + y**2*z],
- x**2 + y**2)
- # compare local order
- assert not contains([x*(1 + x + y), y*(1 + z)], x)
- assert not contains([x*(1 + x + y), y*(1 + z)], x + y)
- def test_SubModulePolyRing_nontriv_local():
- R = QQ.old_poly_ring(x, y, z, order=ilex)
- F = R.free_module(1)
- def contains(I, f):
- return F.submodule(*[[g] for g in I]).contains([f])
- assert contains([x, y], x)
- assert contains([x, y], x + y)
- assert not contains([x, y], 1)
- assert not contains([x, y], z)
- assert contains([x**2 + y, x**2 + x], x - y)
- assert not contains([x + y + z, x*y + x*z + y*z, x*y*z], x**2)
- assert contains([x*(1 + x + y), y*(1 + z)], x)
- assert contains([x*(1 + x + y), y*(1 + z)], x + y)
- def test_syzygy():
- R = QQ.old_poly_ring(x, y, z)
- M = R.free_module(1).submodule([x*y], [y*z], [x*z])
- S = R.free_module(3).submodule([0, x, -y], [z, -x, 0])
- assert M.syzygy_module() == S
- M2 = M / ([x*y*z],)
- S2 = R.free_module(3).submodule([z, 0, 0], [0, x, 0], [0, 0, y])
- assert M2.syzygy_module() == S2
- F = R.free_module(3)
- assert F.submodule(*F.basis()).syzygy_module() == F.submodule()
- R2 = QQ.old_poly_ring(x, y, z) / [x*y*z]
- M3 = R2.free_module(1).submodule([x*y], [y*z], [x*z])
- S3 = R2.free_module(3).submodule([z, 0, 0], [0, x, 0], [0, 0, y])
- assert M3.syzygy_module() == S3
- def test_in_terms_of_generators():
- R = QQ.old_poly_ring(x, order="ilex")
- M = R.free_module(2).submodule([2*x, 0], [1, 2])
- assert M.in_terms_of_generators(
- [x, x]) == [R.convert(Rational(1, 4)), R.convert(x/2)]
- raises(ValueError, lambda: M.in_terms_of_generators([1, 0]))
- M = R.free_module(2) / ([x, 0], [1, 1])
- SM = M.submodule([1, x])
- assert SM.in_terms_of_generators([2, 0]) == [R.convert(-2/(x - 1))]
- R = QQ.old_poly_ring(x, y) / [x**2 - y**2]
- M = R.free_module(2)
- SM = M.submodule([x, 0], [0, y])
- assert SM.in_terms_of_generators(
- [x**2, x**2]) == [R.convert(x), R.convert(y)]
- def test_QuotientModuleElement():
- R = QQ.old_poly_ring(x)
- F = R.free_module(3)
- N = F.submodule([1, x, x**2])
- M = F/N
- e = M.convert([x**2, 2, 0])
- assert M.convert([x + 1, x**2 + x, x**3 + x**2]) == 0
- assert e == [x**2, 2, 0] + N == F.convert([x**2, 2, 0]) + N == \
- M.convert(F.convert([x**2, 2, 0]))
- assert M.convert([x**2 + 1, 2*x + 2, x**2]) == e + [0, x, 0] == \
- e + M.convert([0, x, 0]) == e + F.convert([0, x, 0])
- assert M.convert([x**2 + 1, 2, x**2]) == e - [0, x, 0] == \
- e - M.convert([0, x, 0]) == e - F.convert([0, x, 0])
- assert M.convert([0, 2, 0]) == M.convert([x**2, 4, 0]) - e == \
- [x**2, 4, 0] - e == F.convert([x**2, 4, 0]) - e
- assert M.convert([x**3 + x**2, 2*x + 2, 0]) == (1 + x)*e == \
- R.convert(1 + x)*e == e*(1 + x) == e*R.convert(1 + x)
- assert -e == [-x**2, -2, 0]
- f = [x, x, 0] + N
- assert M.convert([1, 1, 0]) == f / x == f / R.convert(x)
- M2 = F/[(2, 2*x, 2*x**2), (0, 0, 1)]
- G = R.free_module(2)
- M3 = G/[[1, x]]
- M4 = F.submodule([1, x, x**2], [1, 0, 0]) / N
- raises(CoercionFailed, lambda: M.convert(G.convert([1, x])))
- raises(CoercionFailed, lambda: M.convert(M3.convert([1, x])))
- raises(CoercionFailed, lambda: M.convert(M2.convert([1, x, x])))
- assert M2.convert(M.convert([2, x, x**2])) == [2, x, 0]
- assert M.convert(M4.convert([2, 0, 0])) == [2, 0, 0]
- def test_QuotientModule():
- R = QQ.old_poly_ring(x)
- F = R.free_module(3)
- N = F.submodule([1, x, x**2])
- M = F/N
- assert M != F
- assert M != N
- assert M == F / [(1, x, x**2)]
- assert not M.is_zero()
- assert (F / F.basis()).is_zero()
- SQ = F.submodule([1, x, x**2], [2, 0, 0]) / N
- assert SQ == M.submodule([2, x, x**2])
- assert SQ != M.submodule([2, 1, 0])
- assert SQ != M
- assert M.is_submodule(SQ)
- assert not SQ.is_full_module()
- raises(ValueError, lambda: N/F)
- raises(ValueError, lambda: F.submodule([2, 0, 0]) / N)
- raises(ValueError, lambda: R.free_module(2)/F)
- raises(CoercionFailed, lambda: F.convert(M.convert([1, x, x**2])))
- M1 = F / [[1, 1, 1]]
- M2 = M1.submodule([1, 0, 0], [0, 1, 0])
- assert M1 == M2
- def test_ModulesQuotientRing():
- R = QQ.old_poly_ring(x, y, order=(("lex", x), ("ilex", y))) / [x**2 + 1]
- M1 = R.free_module(2)
- assert M1 == R.free_module(2)
- assert M1 != QQ.old_poly_ring(x).free_module(2)
- assert M1 != R.free_module(3)
- assert [x, 1] in M1
- assert [x] not in M1
- assert [1/(R.convert(x) + 1), 2] in M1
- assert [1, 2/(1 + y)] in M1
- assert [1, 2/y] not in M1
- assert M1.convert([x**2, y]) == [-1, y]
- F = R.free_module(3)
- Fd = F.submodule([x**2, 0, 0], [1, 2, 0], [1, 2, 3])
- M = F.submodule([x**2 + y**2, 1, 0], [x, y, 1])
- assert F == Fd
- assert Fd == F
- assert F != M
- assert M != F
- assert Fd != M
- assert M != Fd
- assert Fd == F.submodule(*F.basis())
- assert Fd.is_full_module()
- assert not M.is_full_module()
- assert not Fd.is_zero()
- assert not M.is_zero()
- assert Fd.submodule().is_zero()
- assert M.contains([x**2 + y**2 + x, -x**2 + y, 1])
- assert not M.contains([x**2 + y**2 + x, 1 + y, 2])
- assert M.contains([y**2, 1 - x*y, -x])
- assert F.submodule([x, 0, 0]) == F.submodule([1, 0, 0])
- assert not F.submodule([y, 0, 0]) == F.submodule([1, 0, 0])
- assert F.submodule([1, 0, 0], [0, 1, 0]).union(F.submodule([0, 0, 1])) == F
- assert not M.is_submodule(0)
- def test_module_mul():
- R = QQ.old_poly_ring(x)
- M = R.free_module(2)
- S1 = M.submodule([x, 0], [0, x])
- S2 = M.submodule([x**2, 0], [0, x**2])
- I = R.ideal(x)
- assert I*M == M*I == S1 == x*M == M*x
- assert I*S1 == S2 == x*S1
- def test_intersection():
- # SCA, example 2.8.5
- F = QQ.old_poly_ring(x, y).free_module(2)
- M1 = F.submodule([x, y], [y, 1])
- M2 = F.submodule([0, y - 1], [x, 1], [y, x])
- I = F.submodule([x, y], [y**2 - y, y - 1], [x*y + y, x + 1])
- I1, rel1, rel2 = M1.intersect(M2, relations=True)
- assert I1 == M2.intersect(M1) == I
- for i, g in enumerate(I1.gens):
- assert g == sum(c*x for c, x in zip(rel1[i], M1.gens)) \
- == sum(d*y for d, y in zip(rel2[i], M2.gens))
- assert F.submodule([x, y]).intersect(F.submodule([y, x])).is_zero()
- def test_quotient():
- # SCA, example 2.8.6
- R = QQ.old_poly_ring(x, y, z)
- F = R.free_module(2)
- assert F.submodule([x*y, x*z], [y*z, x*y]).module_quotient(
- F.submodule([y, z], [z, y])) == QQ.old_poly_ring(x, y, z).ideal(x**2*y**2 - x*y*z**2)
- assert F.submodule([x, y]).module_quotient(F.submodule()).is_whole_ring()
- M = F.submodule([x**2, x**2], [y**2, y**2])
- N = F.submodule([x + y, x + y])
- q, rel = M.module_quotient(N, relations=True)
- assert q == R.ideal(y**2, x - y)
- for i, g in enumerate(q.gens):
- assert g*N.gens[0] == sum(c*x for c, x in zip(rel[i], M.gens))
- def test_groebner_extendend():
- M = QQ.old_poly_ring(x, y, z).free_module(3).submodule([x + 1, y, 1], [x*y, z, z**2])
- G, R = M._groebner_vec(extended=True)
- for i, g in enumerate(G):
- assert g == sum(c*gen for c, gen in zip(R[i], M.gens))
|